1y+-4x=

Simple and best practice solution for 1y+-4x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1y+-4x= equation:


Simplifying
1y + -4x = 0

Reorder the terms:
-4x + 1y = 0

Solving
-4x + 1y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1y' to each side of the equation.
-4x + 1y + -1y = 0 + -1y

Combine like terms: 1y + -1y = 0
-4x + 0 = 0 + -1y
-4x = 0 + -1y
Remove the zero:
-4x = -1y

Divide each side by '-4'.
x = 0.25y

Simplifying
x = 0.25y

See similar equations:

| 8v-18=26+3v | | 18+4(-4)= | | 50-40x=200 | | 3t-t=20 | | X^5-2x^4+x^3-x^2+2x-1=0 | | 50+40x=200 | | 5a-2b=8displayngb | | 7+3k-4k=-5-3k | | -5g+1=7+2a | | 2n^3-24n^2-23048=0 | | 2y-4=10x | | 7T+8(7T+2)= | | 4(k+5)=2(9k-2) | | 24xy+6y=0 | | 9n-4n=4n+2n+7 | | 2(8n+6)=-3+n | | 5a-2b=8 | | 3c+2(4)=2 | | 21(7-y)+4=-4 | | 2(x-3)+2X=-14 | | 7-3(5-3v)-8=67 | | 6c=c | | x-6-26=7(x-26) | | Y+7-2=-5 | | x-6+26=7(x+26) | | 8(3B+5)+2= | | X^4-10*X^2-3*X+25=0 | | 5n-2n=9 | | 14d-43=-13-7d | | 70+4y=130 | | -4x+20=-4-x | | 2(5a+6)=2(3a+8) |

Equations solver categories